Aggravation of cardiac myofibroblast arrhythmogeneicity by mechanical stress. (24th October 2014) - Grand, Teddy; Salvarani, Nicolò; Jousset, Florian; Rohr, Stephan
Abstract: Aims: Myofibroblasts (MFBs) as appearing in the myocardium during fibrotic remodelling induce slow conduction following heterocellular gap junctional coupling with cardiomyocytes (CMCs) in bioengineered tissue preparations kept under isometric conditions. In this study, we investigated the hypothesis that strain as developed during diastolic filling of the heart chambers may modulate MFB-dependent slow conduction. Methods and results: Effects of defined levels of strain on single-cell electrophysiology (patch clamp) and impulse conduction in patterned growth cell strands (optical mapping) were investigated in neonatal rat ventricular cell cultures (Wistar) grown on flexible substrates. While 10.5% strain only minimally affected conduction times in control CMC strands (+3.2%, n.s.), it caused a significant slowing of conduction in the fibrosis model consisting of CMC strands coated with MFBs (conduction times +26.3%). Increased sensitivity to strain of the fibrosis model was due to activation of mechanosensitive channels (MSCs) in both CMCs and MFBs that aggravated the MFB-dependent baseline depolarization of CMCs. As found in non-strained preparations, baseline depolarization of CMCs was partly due to the presence of constitutively active MSCs in coupled MFBs. Constitutive activity of MSCs was not dependent on the contractile state of MFBs, because neither stimulation (thrombin) nor suppression (blebbistatin) thereof significantly affected conduction velocities in the non-strained fibrosis model. Conclusions: The findings demonstrate that both constitutive and strain-induced activity of MSCs in MFBs significantly enhance their depolarizing effect on electrotonically coupled CMCs. Ensuing aggravation of slow conduction may contribute to the precipitation of strain-related arrhythmias in fibrotically remodelled hearts.